STUDY OF FACTORS AFFECTING LABOUR PRODUCTIVITY AT A MANNING MARKET IN THE COLOMBO, SRI LANKA - N. C., Weeraratne; M. H., Silva (International Journal For Research In Business, Management And Accounting, 2017)
Sri Lanka is a labour oriented developing country. There are excess labour resources. Labour productivity is the one of the major concepts of human resource management. The purpose of this study was to determine the factors affecting labour productivity in Manning Market. Therefore, the main objective of this research is to investigate and quantify the effects and relative influence of the factors which highly affecting in determining the labour productivity. Furthermore to identify the factors this improves the labour productivity and also identifies the labour problems in Manning Market. To achieve the above objectives, the targeted population of the Manning Market is 1178 stoles for this study. Applying the random sample as a sampling technique, 100 stole has selected for further study. Primary data were collected by using the questionnaire method and analyzed has done by applying the multiple regression model and chi square analysis. As a result of the regression model, 9 variables are highly significant in the productivity. Such as salary satisfaction, absenteeism, quality of good, experience, less competition etc. The findings show the significant effects of these factors and reasons for that. As a result of the chi square test 7 variables are significant in the replacement of Manning Market in Paliyagoda area. Such as job security, government law, working environment change, lack of facility, poor working environment, storage location and shortage of water and power. The results of the chi square test help to determine the labour problems in Manning Market. Findings from this study can be used to development of labour attitudes and decision making process.